2015
DOI: 10.1021/acs.est.5b02275
|View full text |Cite
|
Sign up to set email alerts
|

Methane Emissions from United States Natural Gas Gathering and Processing

Abstract: New facility-level methane (CH4) emissions measurements obtained from 114 natural gas gathering facilities and 16 processing plants in 13 U.S. states were combined with facility counts obtained from state and national databases in a Monte Carlo simulation to estimate CH4 emissions from U.S. natural gas gathering and processing operations. Total annual CH4 emissions of 2421 (+245/-237) Gg were estimated for all U.S. gathering and processing operations, which represents a CH4 loss rate of 0.47% (±0.05%) when nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
109
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 19 publications
7
109
1
Order By: Relevance
“…Dual-tracer release measurements of gathering stations were made previously in a national study by Mitchell et al (2015); however, no on-site or aircraft measurements were made. These measurements were used by Marchese et al (2015) to develop a national estimate of CH 4 emissions from gathering stations, which indicates an average emission rate of 53,066 scf/day (43 kg/h) per station. The influence of tank venting on the average FLER for 31 gathering stations measured by tracer in this study was evaluated in S8.…”
Section: Resultsmentioning
confidence: 99%
“…Dual-tracer release measurements of gathering stations were made previously in a national study by Mitchell et al (2015); however, no on-site or aircraft measurements were made. These measurements were used by Marchese et al (2015) to develop a national estimate of CH 4 emissions from gathering stations, which indicates an average emission rate of 53,066 scf/day (43 kg/h) per station. The influence of tank venting on the average FLER for 31 gathering stations measured by tracer in this study was evaluated in S8.…”
Section: Resultsmentioning
confidence: 99%
“…Data for compressor station locations and emissions come from a data set used in Marchese et al (2015). A total of 489 compressor facilities are listed for Pennsylvania, with 87 % of the listed facilities also containing location data.…”
Section: Regional Methane Emission Inventorymentioning
confidence: 99%
“…Emissions for each compressor station are calculated through two different methodologies. In the simplest case, a flat emission rate of 32.35 kg h −1 is applied to each station, which is the mean emission rate of a gathering facility in PA found in Marchese et al (2015). In the more complex scenario, the same emissions total is used as in the flat rate case but is distributed among the compressor stations linearly as a function of their energy usage.…”
Section: Regional Methane Emission Inventorymentioning
confidence: 99%
“…Methane, the main component of natural gas, is a more potent GHG gas than CO 2 as methane produces 21 times of trapped heat in the atmosphere when compared to CO 2 [2]. Several methane emissions studies have been reported as direct measurements from different natural gas supply chain facilities (exploration, production, gathering, processing,transmission, and distribution) with a variety of CH4 emission sources including fugitive, venting, and combustion emissions for objects in United States [3,4,5]. These studies basically estimate and calculate new emission factors based on direct measurements and mostly refer to The Environmental Protection Agency (EPA) Greenhouse Gas Inventory (GHGI) in comparing their calculation results.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment result was then developed to extrapolate emission factors of Russian long distance gas transmission pipeline. However, these studies [3,4,5,6] had not assessed the variation of natural gas throughput and its contribution to emissions level, both fugitive and venting emissions.…”
Section: Introductionmentioning
confidence: 99%